Coupled piezoelectric-circuit FEA to study influence of a resistive load on power output of piezoelectric energy devices - Zhu, Meiling; Worthington, Emma; Njuguna, James A. K. (Cranfield University, 2012)
This paper presents, for the first time, a coupled piezoelectric-circuit finite element model (CPC-FEM) to analyze the power output of vibration-based piezoelectric energy harvesting devices (EHDs) when connected to a resistive load. Special focus is given to the effect of the resistive load value on the vibrational amplitude of the piezoelectric EHDs, and thus on the current, voltage, and power generated by the EHDs, which are normally assumed to be independent of the resistive load in order to reduce the complexity of modelling and simulation. The CPC-FEM presented uses a cantilever with the sandwich structure and a seismic mass attached to the tip to study the following load characteristics of the EHD as a result of changing the load resistor value: (1) the electric outputs of the EHD: current and voltage, (2) the power dissipated by the resistive load, (3) the vibration amplitude of tip displacement, and (4) the shift in resonant frequency of the cantilever. Significant dependences of the characteristics of the piezoelectric EHDs on the externally connected resistive load are found, rather than independency, as previously assumed in most literature. The CPC-FEM is capable of predicting the generated power output with different resistive load values while simultaneously considering the effect of the resistor value on the vibration amplitude. The CPC-FEM is invaluable for validating the performance of a device before fabrication and testing, thereby reducing the recurring costs associated with repeat fabrication and trials, and also for optimizing device design for maximal power-output generation.